Making the illusory correlation effect appear and then disappear the effects of increased learning - Murphy, Robin A.; Schmeer, Stefanie; Vallee-Tourangeau, Frederic; Mondragon, Esther; Hilton, Denis (2010)
The acquisition of a negative evaluation of fictitious minority social group in spite of the absence of any objective correlation between group membership and negative behaviors was described by Hamilton and Gifford (1976) as an instance of an illusory correlation. We studied the acquisition and attention through time of this correlation learning effect. In two experiments we asked for participants' judgments of two fictitious groups using an online version of a group membership belief paradigm. We tested how judgments of the two groups changed as a function of the amount training they received. Results suggest that the perception of the illusory correlation effect is initially absent emerges with intermediate amounts of absolute experience, but diminishes and is eliminated with increased experienced. This illusory correlation effect can be considered to reflect incomplete learning rather a bias due to information loss in judgments or distinctiveness.